IMPACT OF TRANSFORMATIONAL LEADERSHIP, CHARACTERISTICS OF JOB, AND CAREER DEVELOPMENT ON EMPLOYEE ENGAGEMENT - KUSTIADI BASUKI (Jurnal MoZaiK, 2018)
AbstractAt the company's business development, there is a matter of applying leadership behaviors, characteristics of jobs and career development, thus resulting in employee engagement problems. Employee engagement is very important for the progress of the company's business, because employee engagement can have an impact on job satisfaction, performance, and intentions to quit that will ultimately affect the company's business processes. This study aims to examine the effect of transformational leadership, job characteristic, and career development on employee engagement. The method of this study is survey. The population of this study are all staff of the Finance Company Head Office (129 employees), with sampling method is census, which means that all members of the population used as a sample. The method of analysis used in this study is multiple linear regressions. The result showed that transformational leadership, job characteristic, and career development simultaneously are having significant influence to the employee engagement. Partially, Transformational Leadership and Job Characteristics having significant influence to the Employee Engagement, while Career Development is not having significant influence to the Employee Engagement.Keywords : Transformational Leadership; Job Characteristic; Career Development; Employee Engagement.